Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing


  • 3 years ago

\[(x-1)y''+y'=0\] \[y=\sum_{n=0}^{\infty} a_n x^n\] \[y'=\sum_{n=1}^{\infty} a_n x^{n-1}\] \[y''=\sum_{n=2}^{\infty} n(n-1)a_n x^{n-2}\]

  • This Question is Closed
  1. JenniferSmart1
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    \[xy''-y''+y'=0\] \[x\sum_{n=2}^{\infty}n(n-1)a_nx^{n-2}-\sum_{n=2}^{\infty}n(n-1)a_nx^{n-2}+\sum_{n=1}^{\infty} a_n x^{n-1}=0\]

  2. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy